2017
DOI: 10.1111/dom.13141
|View full text |Cite
|
Sign up to set email alerts
|

Targeting postprandial glycaemia in children with diabetes: Opportunities and challenges

Abstract: Postprandial glycaemia makes a substantial contribution to overall glycaemic control in diabetes, particularly in patients whose preprandial glycaemia is relatively well controlled and glycated haemoglobin (HbA1c) only modestly elevated. Our review addresses the determinants of postprandial glycaemia and how it may be targeted therapeutically in children with diabetes. Postprandial glycaemia is influenced by preprandial glycaemia, macronutrients and their absorption, insulin delivery and sensitivity, the actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 132 publications
(228 reference statements)
0
1
0
Order By: Relevance
“…Moreover, partial antrum resection is capable of destroying antral innervation coordination, which is also a factor leading to gastric emptying [78]. Many previous studies have indicated that gastric emptying can have a substantial influence on the regulation of postprandial glycemia [82][83][84].…”
Section: Gastrointestinal Motility Adjustmentmentioning
confidence: 99%
“…Moreover, partial antrum resection is capable of destroying antral innervation coordination, which is also a factor leading to gastric emptying [78]. Many previous studies have indicated that gastric emptying can have a substantial influence on the regulation of postprandial glycemia [82][83][84].…”
Section: Gastrointestinal Motility Adjustmentmentioning
confidence: 99%